Right Internal Mammary Artery Implantation into Right Ventricular Myocardium for Revascularization of the Entire Heart: Experimental Data and Preliminary Report - Vineberg, Arthur M. (1966)
The left internal mammary artery implant combined with epicardiectomy and free omental graft provides three extra-coronary sources of blood. This operation tested in dogs with 92% main-stem occlusion of three coronary arteries protected 75% of the animals. Applied clinically in over 100 patients, the operation resulted in 90% improvement. To obtain complete myocardial revascularization, the right internal mammary artery has been used as a fourth source of extra-coronary blood. In 57 animals, the right internal mammary arteries were implanted into the anterior walls of the right ventricle; in 80% this vessel formed anastomoses with the right coronary tree, and in 65% with the right and left coronary arteriolar systems. Six patients are described who underwent right internal mammary artery implantation; five of these in addition had the combined operation of left internal mammary artery implant, epicardiectomy and free omental graft. All patients had completely blocked right coronary arteries; in addition, five had advanced disease of the left coronary arterial tree.